PREVALENCE OF PARATUBERCULOSIS IN CATTLE AND BUFFALOES IN FAISALABAD AND ASSOCIATED RISK FACTORS - Aziz-ur-Rehman; M. T. Javed; F. Rizvi; M. N. Khan (Journal of Animal and Plant Sciences, 2017)
Bovine Paratuberculosis is a chronic disease primarily of the gastrointestinal tract. The disease is caused by Mycobacterium avium subsp. Paratuberculosis (MAP). Paratuberculosis is a disease of high economic importance around the globe. The present study was carried out to investigate the prevalence and pathology of paratuberculosis in cattle and buffaloes at two cattle/buffalo colonies of Faisalabad. A total of 133 and 132 adult cattle and buffaloes above two years of age were screened with tuberculin testing for Paratuberculosis. Blood and fecal samples of all the tuberculin positive animals along with the same number of apparently disease-free animals and suspected cases for paratuberculosis (negative by tuberculin test but having chronic diarrhea) were collected and processed for enzyme-linked immunosorbent assay (ELISA) and Ziehl Neelsen (ZN) staining. The study revealed that at two cattle colonies the herd prevalence was 100% and overall animal level prevalence of disease in eight herds was 5.66%. The prevalence rate was non-significantly different in cattle (5.88%) and buffaloes (5.56%). Multivariate logistic regression analysis with the backward elimination procedure in cattle and buffaloes revealed that herd (OR=0.294), age (OR=1.16) and lactation number (OR=1.534) showed significant association with the occurrence of Paratuberculosis. The study revealed that the disease was present at these two cattle/buffalo colonies. The ELISA and ZN showed more positive cases than that of tuberculin testing.
Keywords: Paratuberculosis; Prevalence; ELISA; Cattle; Buffalo